A new name for Emilia flaccida C.Jeffrey (Asteraceae) - Kottaimuthu, Ramalingam; Basu, Muthuramalingam Jothi; Sukanyadevi, Moorthi; Kumar, John Kennedy John Praveen (Phytotaxa, 2020)
Emilia Cassini (1817: 68) is a palaeotropical genus of annual and perennial herbs comprising about 116 species (POWO 2020), the majority of which found in Africa south of the Sahara (Beentje et al. 2005, Nordenstam 2007). In 1986, Jeffrey described Emilia flaccida but he appears to have been unaware of an earlier homonym, E. flaccida Miquel (1856: 102), which already exists for a Sumatran species. Therefore, E. flaccida Jeffrey (1986: 916) is to be treated as an illegitimate later homonym of E. flaccida Miquel (1856: 102). Till now, no legitimate synonym was known to exist for E. flaccida Jeffrey (POWO 2020), hence a new name is proposed here.